2023
DOI: 10.1038/s41598-023-27898-5
|View full text |Cite
|
Sign up to set email alerts
|

HA-tag CD63 is a novel conditional transgenic approach to track extracellular vesicle interactions with sperm and their transfer at conception

Abstract: Extracellular vesicles (EVs) are a unique mode of intercellular communication capable of specificity in transmitting signals and cargo to coordinate local and distant cellular functions. A key example of this is the essential role that EVs secreted by epithelial cells lining the lumen of the male reproductive tract play in post-spermatogenic sperm maturation. We recently showed in a preclinical mouse model that this fundamental process had a causal role in somatic-to-germline transmission of biological informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Next, we verified the involvement of miR‐125b‐5p in the modulation of EV trafficking, focusing on the localization of EV‐related proteins in pTr cells. VPS36 (miR‐125b‐5p target and marker of ESCRT‐II complex present in endosomes/MVBs 47 ) and CD63 (marker of EVs 48 ) were selected based on our recent studies pointing to embryonic signals as triggers of EV trafficking in endometrial luminal epithelial cells 26 . Regions of interest (ROIs) were set based on the overlapping localization of both proteins present in the highly visible and well‐shaped cell borders (white) in comparison to the whole cell (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we verified the involvement of miR‐125b‐5p in the modulation of EV trafficking, focusing on the localization of EV‐related proteins in pTr cells. VPS36 (miR‐125b‐5p target and marker of ESCRT‐II complex present in endosomes/MVBs 47 ) and CD63 (marker of EVs 48 ) were selected based on our recent studies pointing to embryonic signals as triggers of EV trafficking in endometrial luminal epithelial cells 26 . Regions of interest (ROIs) were set based on the overlapping localization of both proteins present in the highly visible and well‐shaped cell borders (white) in comparison to the whole cell (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…This sentiment was corroborated by a different group where changes in sperm miRNA were much more prevalent 12 weeks after four weeks of chronic randomised psychological stress as opposed to one week after, concluding that they had been taken up during epididymal transit, which requires two weeks in mouse [49]. Tracking EVs using a novel labelling approach based on an HAtagged tetraspanin endogenous to EVs, the authors showed EV content to be taken up and present within sperm heads [50]. Conversely, a recent study proposed that the majority of non-coding RNA in sperm is acquired from cytoplasmic droplets, transient organelles storing RNA specifically in testicular and epididymal sperm [51].…”
Section: Non-coding Rnasmentioning
confidence: 88%
“…4.4 CD63 and VPS36 showed spatial-dependent colocalization and correlation after miRNA delivery Next, we verified the involvement of miR-125b-5p in the modulation of EV trafficking, focusing on the localization of EV-related proteins in pTr cells. VPS36 (miR-125b-5p target and marker of ESCRT-II complex present in endosomes/MVBs [47]) and CD63 (marker of EVs [48]) were selected based on our recent studies pointing to embryonic signals as triggers of EV trafficking in endometrial luminal epithelial cells [26]. Regions of interest (ROIs) were set based on the overlapping localization of both proteins present in the highly visible and well-shaped cell borders (white) in comparison to the whole cell (Fig.…”
Section: Mir-125b-5p Is Efficiently Delivered To Ptr Cells and Intern...mentioning
confidence: 99%